Emergency physician risk of occupational mortality: A scoping review. Issue 5 (4th October 2021) - Goolsby, Craig; Lala, Vidya; Gebner, Riley; Dacuyan‐Faucher, Nicole; Charlton, Nathan; Schuler, Keke
Abstract: Background: Occupational hazards for emergency physicians are widely known, but the risk of work‐related mortality is not clear. The COVID‐19 pandemic generated new concerns about the risk of occupational mortality, particularly in the setting of inadequate personal protective equipment. The perception of increased risk generated ethical concerns regarding emergency physicians' duty to treat and employers' duty to protect their employees. We performed this scoping review to define prepandemic emergency physician occupational mortality. Methods: We performed a scoping review of peer‐reviewed publications from PubMed, EMBASE, and Cochrane databases in September 2020. Results: Of the 747 unique articles identified in the 3 databases, 1 article met inclusion criteria and was included in the final analysis. Conclusion: The baseline risk of occupational mortality for emergency physicians is not established in the scientific literature. Further study is needed to quantify risk, as this information would be useful to shape policy and ethical considerations.